Stunting Prevention in Toddlers in Village Baros District Serang Banten Province - Sumarni, Aan; Novelia, Shinta; Puspitasari, Desi; Ernawati; Halimatusadiya; Yuliarti, Reni (Rajaki of Tulip Medika Publisher, 2024)
Stunting is a condition in which children under five years of age or toddlers experience growth failure caused by a lack of nutrition received by the fetus/infant. The condition of children who are stunted can be seen from their height which is below the height standard for their age, their bone growth is below the high standard for their age, their bone growth is delayed and their body weight is low for their age. The purpose of doing community service is to apply scientific theories in the health sector to overcome problems that occur in the field so that they can benefit the community, actively participate in the health development process, increase community empowerment in the health sector, increase the ability of the academic community to apply theories science both independently and in groups, helping to overcome problems faced by the government and society with practical scientific methods. Following up on the problems found in Sinarmukti Village, Baros District, Serang Regency, where stunted toddlers were found, it is necessary to carry out health education about stunting, the impact and prevention of stunting by evaluating anthropometric measurements of toddlers and providing pumpkin tray cakes to improve nutrition in toddlers. Service implementation activities run smoothly. Out of the 17 toddlers who took part in the activity, there were 29.4% (5) of them who were stunted. The community is very enthusiastic and appreciates this activity, because they know the importance of maintaining nutrition, growth and development of their toddlers. The strategy to improve nutrition for toddlers is to take advantage of the abundant natural resources in the area, this time by consuming pumpkin trays and increasing parental knowledge in maintaining children's nutrition, growth and development. Keywords: stunting, prevention, toddlers